The Bird Resources of Medieval Novgorod - Sheila Hamilton-dyer (2002)
Abstract. This paper summarises recent studies on bones from Novgorod The Great, and the nearby settlement of Ryurik Gorodishche, in north-west Russia. Bird bones are fre-quently collected along with the mammal bones. Preliminary findings have indicated that ducks and chickens were the most common birds utilized, with the latter possibly growing in importance in the later levels. Situated where the river Volkov flows north out of Lake Ilmen, the wetland environment of the settlement is reflected in the high number of water-fowl in the assemblages. Other species include game-birds, raptors, and corvids. There is some indication of hawking and perhaps of captive wild birds. Wet-sieving trials have re-vealed that bird bones are under represented and that there is also some bias in favour of the larger species and elements. Detailed analysis of the bones from Gorodishche showed a similar, although less diverse, species representation to that in the main town. Analysis includes the collection of metrical, anatomical, and butchery data and it is intended that this preliminary work should form the basis of more detailed analyses, including intra-site and diachronic comparisons, both at Novgorod and in the region as a whole.